Glass

A glass substrate with specific compositional and physical properties addresses warpage and molding challenges, enhancing moldability and reducing manufacturing costs for large, thin substrates.

JP7605280B2Active Publication Date: 2024-12-24AGC INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023199180
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-14
Filing Date
2023-11-24
Publication Date
2024-12-24
Estimated Expiration
2039-03-13

Smart Images

  • Figure 0007605280000001
    Figure 0007605280000001
  • Figure 0007605280000002
    Figure 0007605280000002
  • Figure 0007605280000003
    Figure 0007605280000003
Patent Text Reader

Abstract

To provide a glass capable of suppressing deformation of a glass substrate such as warp, being excellent in molding properties, causing less load on a production apparatus, and facilitating production of a large sized and thin glass substrate.SOLUTION: Glass according to the present invention is configured so that its density, Young modulus, strain point, temperature T4 at which the glass viscosity is 104 dPa s, a glass surface devitrification temperature (Tc) and thermal expansion coefficient are in prescribed ranges. A content of at least one kind of an alkali metal oxide selected from SiO2, Al2O3, Li2O, Na2O and K2O and a content of P2O5 are in prescribed ranges.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass suitable for use as a glass substrate for various displays, photomasks, electronic device supports, information recording media, planar antennas, and the like. [Background technology]

[0002] Glass plates (glass substrates) for various displays, photomasks, electronic device supports, information recording media, and flat antennas, particularly glass used for glass plates on whose surfaces a thin film of metal or oxide is formed, are required to have the following properties (1) to (4). (1) When the glass contains an alkali metal oxide, the alkali metal ions diffuse into the thin film and deteriorate the film properties of the thin film, so the glass must be substantially free of alkali metal ions. (2) The glass sheet must have a high strain point so that deformation of the glass sheet and shrinkage (thermal shrinkage) associated with stabilization of the glass structure can be minimized when the glass sheet is exposed to high temperatures during the thin film formation process.

[0003] (3) It has sufficient chemical durability against various chemicals used in semiconductor formation. In particular, SiO x and SiN x It must be durable against buffered hydrofluoric acid (BHF: a mixture of hydrofluoric acid and ammonium fluoride) used in etching of SiO2, chemical solutions containing hydrochloric acid used in etching ITO, various acids (nitric acid, sulfuric acid, etc.) used in etching metal electrodes, and alkalis used in resist stripping solutions. (4) There are no internal or surface defects (bubbles, veins, inclusions, pits, scratches, etc.).

[0004] In addition to the above requirements, the following requirements (5) to (9) have also been made in recent years. (5) Since displays need to be lightweight, glass with a low specific gravity is desirable. (6) Since displays are required to be lighter, thinner glass sheets are desirable. (7) In addition to the amorphous silicon (a-Si) type liquid crystal displays used up until now, polycrystalline silicon (p-Si) type liquid crystal displays, which require a higher heat treatment temperature, are now being manufactured (heat treatment temperature for a-Si: approximately 350°C, heat treatment temperature for p-Si: 350-550°C), so heat resistance is required.

[0005] (8) Glass with a small average thermal expansion coefficient is required for the purpose of increasing productivity by increasing the temperature rise and fall speed in heat treatment during the production of liquid crystal displays and for the purpose of increasing thermal shock resistance. On the other hand, if the average thermal expansion coefficient of glass is too small, the glass will warp significantly when the number of film formation processes, such as gate metal film and gate insulating film formation processes, increases during the production of liquid crystal displays, causing problems such as cracks and scratches during transportation of the liquid crystal displays and large deviations in the exposure pattern. (9) Furthermore, as glass substrates become larger and thinner, there is a demand for glass with a high specific elastic modulus (Young's modulus / density).

[0006] In order to satisfy the above-mentioned requirements, various glass compositions have been proposed so far, for example, for glass for liquid crystal display panels (see Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent No. 5702888 [Patent Document 2] International Publication No. 2013 / 183626 [Patent Document 3] Japanese Patent No. 5849965 [Patent Document 4] Japanese Patent No. 5712922 Summary of the Invention [Problem to be solved by the invention]

[0008] In recent years, electronic displays have become increasingly high-resolution, and in large TVs, the increased definition has led to increased warping of the substrate due to the deposition of various films, for example due to an increase in the thickness of the Cu wiring. This has led to a growing need for substrates with less warping, and in order to meet this need, it is necessary to increase the Young's modulus of glass. However, the known glasses with high Young's modulus as described in Patent Documents 3 and 4 have high strain points and viscosities of 10 4 The devitrification temperature tends to be higher than the temperature T4 at which the glass becomes dPa s. As a result, it becomes difficult to mold the glass, which places a heavy burden on the manufacturing equipment, raising concerns about increased production costs.

[0009] An object of the present invention is to provide a glass that can suppress deformation such as warping of a glass substrate, has excellent formability, imposes a low burden on manufacturing equipment, and facilitates the manufacture of large, thin glass substrates. [Means for solving the problem]

[0010] The glass of the present invention which achieves the above object has a density of 2.60 g / cm 3 The Young's modulus is 88 GPa or more, the strain point is 650 to 720 °C, and the glass viscosity is 10 4 The temperature T4 at which the glass surface becomes dPa·s is 1320°C or lower, and the glass surface devitrification temperature (T c ) is T4+20℃ or less, and the average thermal expansion coefficient at 50 to 350℃ is 30×10 -7 ~43×10 -7 / °C, and contains, in mole % on an oxide basis, 50 to 80% SiO2, 8 to 20% Al2O3, 0 to 0.5% in total of at least one alkali metal oxide selected from the group consisting of Li2O, Na2O and K2O, and 0 to 1% P2O5.

[0011] In one embodiment of the alkali-free glass of the present invention, the specific elastic modulus may be 34 MN·m / kg or more.

[0012] In one embodiment of the alkali-free glass of the present invention, the glass surface devitrification viscosity (η c ) is 10 3.8It may be dPa·s or more.

[0013] In one embodiment of the alkali-free glass of the present invention, the viscosity is 10 2 The temperature T2 at which the thermal expansion coefficient dPa·s is reached may be 1680°C or lower.

[0014] In one embodiment of the alkali-free glass of the present invention, the glass transition point may be 730 to 790°C.

[0015] One embodiment of the alkali-free glass of the present invention is a glass having a composition expressed in mole percent based on oxides. SiO2 50-80%, Al2O3 8-20%, B2O3 0-5%, MgO 0-15%, CaO 0-12%, SrO 0-10%, BaO 0-10%, Na2O 0.005-0.2%, F: 0.001 to 0.5%, P2O5 0-1%, Contains 0 to 0.5% in total of at least one alkali metal oxide selected from the group consisting of Li2O, Na2O, and K2O, The content of MgO+CaO+SrO+BaO may be 18 to 22%.

[0016] One embodiment of the alkali-free glass of the present invention may contain, in mole percent on an oxide basis, 0.1 to 15% MgO and 1 to 12% CaO, with an MgO / CaO ratio of 0.7 to 1.33.

[0017] In one embodiment of the alkali-free glass of the present invention, the β-OH value is 0.1 to 0.6 mm -1 may be also possible.

[0018] In one embodiment of the alkali-free glass of the present invention, the value represented by the following formula (I) may be 4.10 or more. (7.87[Al2O3]-8.5[B2O3]+11.35[MgO]+7.09[CaO]+5.52[SrO]-1.45[BaO]) / [SiO2]···Equation (I)

[0019] In one embodiment of the alkali-free glass of the present invention, the value represented by the following formula (II) may be 0.95 or more. {-1.02[Al2O3]+10.79[B2O3]+2.84[MgO]+4.12[CaO]+5.19[SrO]+3.16[BaO] +11.07×([Li2O]+[Na2O]+[K2O])+3.954[F]+5.677[β-OH]} / [SiO2]...Formula (II)

[0020] In one embodiment of the alkali-free glass of the present invention, the value represented by the following formula (III) may be 5.5 or less. (8.9[Al2O3]+4.26[B2O3]+11.3[MgO]+4.54[CaO]+0.1[SrO]-9.98[BaO])×{1+([MgO] / [CaO]-1) 2} / [SiO2]...Formula (III)

[0021] In one embodiment of the alkali-free glass of the present invention, SnO2 may be contained in an amount of 0.5% or less, expressed in mole percent on an oxide basis.

[0022] In one embodiment of the alkali-free glass of the present invention, the compaction may be 100 ppm or less.

[0023] In one embodiment of the alkali-free glass of the present invention, the equivalent cooling rate may be 5 to 500° C. / min.

[0024] One embodiment of the alkali-free glass of the present invention may be a glass plate having at least one side of 1800 mm or more and a thickness of 0.7 mm or less.

[0025] An embodiment of the alkali-free glass of the present invention may be produced by the float process or the fusion process.

[0026] The display panel of the present invention comprises the glass of the present invention.

[0027] The semiconductor device of the present invention also comprises the glass of the present invention.

[0028] The information recording medium of the present invention comprises the glass of the present invention.

[0029] The planar antenna of the present invention comprises the glass of the present invention. Effect of the Invention

[0030] According to the present invention, it is possible to provide glass that can suppress deformation such as warping of a glass substrate, has excellent formability, places a low burden on manufacturing equipment, and facilitates the manufacture of large, thin glass substrates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below. In the following, the composition range of each component of the glass is expressed in mole percent based on the oxide. In the following, the numerical range indicated as "numerical value A to numerical value B" indicates a range including numerical value A and numerical value B as the minimum and maximum values, respectively, and means numerical value A or more and numerical value B or less.

[0032] First, the composition of the glass of this embodiment will be described. If the SiO2 content is less than 50 mol% (hereinafter simply referred to as %), the strain point does not rise sufficiently, and the average thermal expansion coefficient increases, tending to increase the specific gravity. Therefore, the SiO2 content is 50% or more, preferably 62% or more, more preferably 62.5% or more, even more preferably 63% or more, particularly preferably 63.5% or more, and most preferably 64% or more. If the SiO2 content exceeds 80%, the melting property of the glass decreases, the Young's modulus decreases, and the devitrification temperature tends to increase. Therefore, the SiO2 content is 80% or less, preferably 70% or less, more preferably 68% or less, even more preferably 67% or less, particularly preferably 66% or less, and most preferably 65.7% or less.

[0033] Al2O3 increases the Young's modulus to suppress deflection, suppresses phase separation of glass, lowers the average thermal expansion coefficient, raises the strain point, and improves fracture toughness to increase glass strength. If the content of Al2O3 is less than 8%, these effects are unlikely to be achieved, and other components that increase the average thermal expansion coefficient are relatively increased, resulting in a tendency for the average thermal expansion coefficient to be large. Therefore, the content of Al2O3 is 8% or more, preferably 10% or more, more preferably 12% or more, even more preferably 12.5% ​​or more, particularly preferably 12.8% or more, and most preferably 13% or more. If the Al2O3 content exceeds 20%, the melting property of the glass may deteriorate and the devitrification temperature may increase, so the Al2O3 content is 20% or less, preferably 16.5% or less, more preferably 16% or less, further preferably 15% or less, particularly preferably 14.5% or less, and most preferably 14% or less.

[0034] Although B2O3 is not an essential component, it improves BHF resistance, improves the melting reactivity of glass, and lowers the devitrification temperature, so it may be contained in an amount of 6% or less. The content of B2O3 is 6% or less, preferably 5% or less, and more preferably 3% or less. Since B2O3 reduces the Young's modulus, the B2O3 content is more preferably 2.5% or less, more preferably 2.2% or less, even more preferably 2% or less, particularly preferably 1.7% or less, and most preferably 1.5% or less.

[0035] MgO is not an essential component, but since it increases the Young's modulus without increasing the specific gravity, it can be added to increase the specific elastic modulus and suppress deflection, and also to improve the fracture toughness value and increase the glass strength. MgO also improves solubility. If the MgO content is less than 1%, these effects are unlikely to be achieved, and the thermal expansion coefficient may become too low. Therefore, the MgO content is preferably 1% or more, more preferably 7% or more, even more preferably 8% or more, particularly preferably 8.2% or more, and most preferably 8.5% or more. However, if the MgO content is too high, the devitrification temperature is likely to increase, so the MgO content is preferably 15% or less, more preferably 13% or less, further preferably 10% or less, and particularly preferably 9.7% or less.

[0036] CaO is not an essential component, but it has the characteristic of increasing the specific elastic modulus next to MgO among alkaline earth metals and not lowering the strain point too much, and can be added because it also improves solubility like MgO. Furthermore, CaO has the characteristic of being less likely to increase the devitrification temperature than MgO. If the CaO content is less than 1%, these effects are less likely to be achieved. Therefore, the CaO content is preferably 1% or more, more preferably 6% or more, even more preferably 7% or more, particularly preferably 8% or more, and most preferably 8.5% or more. If the CaO content exceeds 12%, the average thermal expansion coefficient becomes too high and the devitrification temperature becomes high, making the glass more susceptible to devitrification during production. Therefore, the CaO content is preferably 12% or less, more preferably 10.5% or less, and even more preferably 10% or less.

[0037] Although SrO is not an essential component, it can be contained since it improves the melting property without increasing the devitrification temperature of the glass. However, if the content of SrO is less than 0.5%, these effects are difficult to obtain. Therefore, the content of SrO is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.2% or more, and particularly preferably 1.5% or more. The above effect of SrO is lower than that of BaO, and if the SrO content is too high, the effect of increasing the specific gravity will be dominant and the average thermal expansion coefficient may become too high. Therefore, the SrO content is preferably 10% or less, more preferably 4% or less, even more preferably 3% or less, and particularly preferably 2% or less.

[0038] Although BaO is not an essential component, it may be contained in the glass of the present embodiment since it improves the solubility without increasing the devitrification temperature of the glass. However, if the content of BaO is excessive, the specific gravity tends to increase, the Young's modulus tends to decrease, and the average thermal expansion coefficient tends to become too large. Therefore, the content of BaO is preferably 10% or less, more preferably 0.5% or less. It is even more preferable that the glass of the present embodiment does not substantially contain BaO. In this specification, "substantially free" means that BaO is not contained except for unavoidable impurities mixed in from raw materials, that is, BaO is not intentionally contained. In this embodiment, the content of BaO when BaO is substantially free is, for example, 0.3% or less, and preferably 0.2% or less.

[0039] If the total amount of alkaline earth metal oxides, i.e., MgO+CaO+SrO+BaO (hereinafter also referred to as "RO"), is small, the devitrification temperature becomes high, i.e., the devitrification viscosity becomes low, and the moldability deteriorates. Therefore, RO is set to 18% or more. If the RO content is too high, the average thermal expansion coefficient may become large and the acid resistance may become poor, so the RO content is 22% or less, preferably 20.7% or less, and more preferably 20.5% or less.

[0040] In addition, when MgO is 1% or more and CaO is 1% or more, if the ratio of the content of MgO to the content of CaO, i.e., MgO / CaO, is small, CaO-Al2O3-SiO2 crystals are easily precipitated, and moldability is deteriorated. Specifically, the devitrification temperature is high, that is, the devitrification viscosity is low. Therefore, MgO / CaO is 0.7 or more, preferably 0.8 or more, more preferably 0.85 or more, even more preferably 0.9 or more, and particularly preferably 0.92 or more. However, if MgO / CaO is too large, MgO-Al2O3-SiO2 crystals are easily precipitated, and the devitrification temperature is high, that is, the devitrification viscosity is low. Therefore, MgO / CaO is 1.33 or less, preferably 1.3 or less, more preferably 1.25 or less, even more preferably 1.2% or less, particularly preferably 1.1% or less, and most preferably 1.05% or less.

[0041] In the glass of the present embodiment, alkali metal oxides are inevitably contained due to raw material impurities and the like, and the inclusion of a very small amount of alkali metal oxides is permitted for the purpose of improving solubility. However, when the glass of this embodiment is used as the TFT side substrate of a flat panel display, if the content of alkali metal oxide is too high, the migration of alkali ions into the TFT element becomes significant, causing the transistor characteristics to become unstable and losing reliability, and therefore the content must be kept within an appropriate range. Furthermore, when the glass of the present embodiment is used as a semiconductor support substrate, if the content of alkali metal oxide is too high, there is a risk that alkali ions will diffuse into the silicon-containing substrate in the heat treatment step of bonding the silicon-containing substrate and the glass substrate together. Therefore, the total amount of alkali metal oxides, i.e., Li2O+Na2O+K2O (hereinafter also referred to as "R'2O"), is 0.5% or less, preferably 0.2% or less, more preferably 0.1% or less, more preferably 0.08% or less, even more preferably 0.05% or less, and most preferably 0.03% or less.

[0042] However, since Na2O has the effect of lowering the strain point of glass, it can be contained within a range that does not cause the above-mentioned problems. In order to obtain the effect of lowering the strain point of glass, the Na2O content is preferably 0.005% or more, more preferably 0.01% or more, particularly preferably 0.015% or more, and most preferably 0.02% or more. However, if a large amount of Na2O is contained, the above-mentioned problems may occur, so the Na2O content is preferably 0.5% or less, more preferably 0.2% or less, even more preferably 0.1% or less, still more preferably 0.08% or less, particularly preferably 0.05% or less, and most preferably 0.03% or less.

[0043] F is not an essential component, but can be contained since it has the effect of lowering the strain point of glass. In order to obtain the effect of lowering the strain point of glass, the F content is preferably 0.001% or more, more preferably 0.01% or more. The upper limit of the F content is not particularly limited, but is preferably 1.5% or less (0.43 mass% or less), and more preferably 0.7% or less.

[0044] If glass contains a large amount of P2O5, the glass may have poor water resistance, may be prone to striae, and may have poor uniformity. In addition, if the glass is used as a display, if the glass contains a large amount of P, there may be a problem of leakage current in the TFT. Therefore, the P2O5 content of the glass of this embodiment is 1% or less. It is preferable that the glass of this embodiment does not substantially contain P2O5. In this embodiment, when the glass does not substantially contain P2O5, the P2O5 content is, for example, 0.01% or less, and preferably 0.005% or less.

[0045] Furthermore, in order to facilitate recycling of the glass, it is preferable that the glass of this embodiment does not substantially contain PbO, As2O3, or Sb2O3. In this embodiment, when the glass does not substantially contain PbO, As2O3, or Sb2O3, the contents of PbO, As2O3, and Sb2O3 are each, for example, 0.01% or less, and preferably 0.005% or less.

[0046] For the purpose of improving the meltability, clarity, formability, etc. of the glass, the glass of the present embodiment may contain one or more of ZrO2, ZnO, Fe2O3, SO3, Cl, and SnO2 in a total amount of 2% or less, preferably 1% or less, and more preferably 0.5% or less. Among these, when SnO2 is contained for the purpose of improving the meltability and clarity of the glass, the content of SnO2 is preferably 0.5% or less (1.1 mass% or less).

[0047] The moisture in glass has the effect of lowering the strain point of the glass. The β-OH value of glass is used as an index of the moisture content in the glass. When the β-OH value of glass is 0.1 to 0.6 mm, -1 It is preferable to lower the strain point of the glass. -1 If the thickness exceeds 0.15 mm, the generation of platinum interface bubbles cannot be suppressed. Platinum interface bubbles are generated when H2 passing through the wall of the molten glass flow channel made of platinum reacts with the moisture in the molten glass to generate O2. The β-OH value of glass is 0.15 to 0.6 mm. -1 More preferably, 0.2 to 0.45 mm -1 More preferably, 0.22 to 0.35 mm -1 is more preferable, and 0.25 to 0.3 mm -1 is more preferred. The β-OH value of the glass can be adjusted by various conditions during melting of the glass raw materials, such as the water content in the glass raw materials, the water vapor concentration in the melting tank, and the residence time of the molten glass in the melting tank. One method for adjusting the water content in glass raw materials is to use hydroxides instead of oxides as glass raw materials (for example, to use magnesium hydroxide (Mg(OH)2) instead of magnesium oxide (MgO) as a magnesium source). In addition, as a method for adjusting the water vapor concentration in the dissolution tank, there is a method of using oxygen or a mixture of oxygen and air instead of air for burning fuels such as city gas or heavy oil to heat the dissolution tank.

[0048] In the glass of the present embodiment, the value represented by the following formula (I) is preferably 4.10 or more. (7.87[Al2O3]-8.5[B2O3]+11.35[MgO]+7.09[CaO]+5.52[SrO]-1.45[BaO]) / [SiO2]···Equation (I) The value represented by formula (I) is an index of Young's modulus, and if this value is less than 4.10, the Young's modulus is low. In the glass of this embodiment, the value represented by formula (I) is more preferably 4.15 or more, further preferably 4.20 or more, particularly preferably 4.25 or more, and most preferably 4.30 or more. In the above formula (I), [Al2O3], [B2O3], [MgO], [CaO], [SrO], [BaO], and [SiO2] respectively represent the contents of Al2O3, B2O3, MgO, CaO, SrO, BaO, and SiO2 in mole percent on an oxide basis. The same applies to the following formulas (II) and (III).

[0049] In the glass of the present embodiment, the value represented by the following formula (II) is preferably 0.95 or more. {-1.02[Al2O3]+10.79[B2O3]+2.84[MgO]+4.12[CaO]+5.19[SrO]+3.16[BaO] +11.07×([Li2O]+[Na2O]+[K2O])+3.954[F]+5.677[β-OH]} / [SiO2]...Formula (II) The value represented by formula (II) is an index of the strain point, and if this value is less than 0.95, the strain point is high. In the glass of this embodiment, the value represented by formula (II) is more preferably 1.0 or more, further preferably 1.05 or more, and particularly preferably 1.10 or more. In the above formula (II), [Li2O], [Na2O], [K2O], and [F] respectively represent the contents of Li2O, Na2O, K2O, and F expressed in mole percent on an oxide basis. In the above formula (II), [β-OH] is mm -1 The units used are β-OH values.

[0050] In the glass of the present embodiment, the value represented by the following formula (III) is preferably 5.5 or less. (8.9[Al2O3]+4.26[B2O3]+11.3[MgO]+4.54[CaO]+0.1[SrO]-9.98[BaO])×{1+([MgO] / [CaO]-1) 2} / [SiO2]...Formula (III) The value represented by formula (III) is an index of the devitrification viscosity, and if this value exceeds 5.5, the devitrification viscosity is low. In the glass of this embodiment, the value represented by formula (III) is more preferably 5.1 or less, further preferably 4.8 or less, particularly preferably 4.5 or less, and most preferably 4.30 or less.

[0051] The Young's modulus of the glass of this embodiment is 88 GPa or more. This suppresses deformation of the substrate due to external stress. For example, in the manufacture of a TFT-side substrate of a flat panel display, warping of the substrate is suppressed when a gate metal film such as copper or a gate insulating film such as silicon nitride is formed on the surface of the substrate. Deflection of the substrate is also suppressed. The Young's modulus is preferably 88.5 GPa or more, more preferably 89 GPa or more, even more preferably 89.5 GPa or more, particularly preferably 90 GPa or more, and most preferably 90.5 GPa or more. The Young's modulus can be measured by an ultrasonic method.

[0052] The density of the glass in this embodiment is 2.60 g / cm 3 This reduces the deflection caused by its own weight, making it easier to handle when it is made into a large substrate. In addition, the device using the glass of this embodiment can be made lighter. The density is 2.59 g / cm 3 Less than 2.58 g / cm is more preferable. 3 More preferably, 2.57 g / cm 3 The following is particularly preferred: 2.56 g / cm 3 The following is most preferred. Note that a large substrate is, for example, a substrate with at least one side of 1800 mm or more. At least one side of the large substrate may be, for example, 2000 mm or more, 2500 mm or more, 3000 mm or more, or 3500 mm or more.

[0053] The glass of this embodiment has a strain point of 650 to 720°C. If the strain point is less than 650°C, deformation of the glass plate and shrinkage (thermal shrinkage) associated with stabilization of the glass structure are likely to occur when the glass plate is exposed to high temperatures in the thin film formation process of the display. The strain point is preferably 685°C or higher, more preferably 690°C or higher, even more preferably 693°C or higher, particularly preferably 695°C or higher, and most preferably 698°C or higher. On the other hand, if the strain point is too high, the temperature of the annealing device needs to be increased accordingly, and the life of the annealing device tends to be shortened. In addition, it becomes difficult to form the glass, and there is a risk that the plate thickness deviation and surface waviness will increase. The strain point is preferably 718°C or lower, more preferably 716°C or lower, even more preferably 714°C or lower, particularly preferably 712°C or lower, and most preferably 710°C or lower.

[0054] The glass of the present embodiment has a viscosity of 10 4 The temperature T4 at which the glass has a viscosity of dPa·s is 1320°C or lower. This provides excellent formability to the glass of this embodiment. This also reduces the burden on the manufacturing equipment. For example, the life of a float bath for forming the glass can be extended, improving productivity. T4 is preferably 1300°C or lower, more preferably 1290°C or lower, even more preferably 1285°C or lower, and particularly preferably 1280°C or lower. T4 is measured using a rotational viscometer according to the method specified in ASTM C 965-96, and the viscosity is 10 4 It can be calculated as the temperature at which the viscosity becomes d·Pa·s. In the examples described below, NBS710 and NIST717a were used as reference samples for calibrating the device.

[0055] The glass of the present embodiment has a glass surface devitrification temperature (T c) is T4+20°C or less. This provides the glass of the present embodiment with excellent formability. This also makes it possible to suppress the occurrence of crystals inside the glass during forming, which would otherwise cause a decrease in transmittance. This also makes it possible to reduce the burden on manufacturing equipment. For example, the life of a float bath for forming the glass can be extended, improving productivity. Glass surface devitrification temperature (T c ) is preferably T4+10°C or lower, more preferably T4+5°C or lower, even more preferably T4°C or lower, particularly preferably T4-1°C or lower, and most preferably T4-5°C or lower. Glass surface devitrification temperature (T c ) and glass internal devitrification temperature (T d The glass surface devitrification temperature (T) can be calculated as follows: crushed glass particles are placed in a platinum dish and heat-treated for 17 hours in an electric furnace controlled at a constant temperature. After the heat treatment, an optical microscope is used to measure the maximum temperature at which crystals precipitate on the glass surface and the minimum temperature at which no crystals precipitate. The average of these values ​​is taken as the glass surface devitrification temperature (T c Similarly, the maximum temperature at which crystals precipitate inside the glass and the minimum temperature at which no crystals precipitate are measured, and the average of these is taken as the glass internal devitrification temperature (T d ) The glass surface devitrification temperature (T c ) and glass internal devitrification temperature (T d ) is obtained by measuring the viscosity of the glass at each devitrification temperature.

[0056] The average thermal expansion coefficient of the glass of this embodiment at 50 to 350°C is 30 × 10 -7 / °C or more. For example, in the manufacture of a TFT-side substrate for a flat panel display, a gate metal film such as copper and a gate insulating film such as silicon nitride may be laminated in this order on glass. In this case, the average thermal expansion coefficient at 50 to 350°C is 30×10 -7 If the temperature is less than 100° C. / ° C., the difference in thermal expansion between the gate metal film, such as copper, formed on the substrate surface will be large, which may cause problems such as substrate warping and film peeling. The average thermal expansion coefficient between 50 and 350°C is 33×10 -7 / ℃ or more is preferable, 35×10 -7 / ℃ or more is preferable, and 36×10 -7 / ℃ or more is more preferable, and 37×10 -7 / ℃ or more is particularly preferable, and 38×10 -7 / °C or higher is most preferable. On the other hand, the average thermal expansion coefficient at 50 to 350°C is 43 × 10 -7 If the temperature exceeds 50°C, the glass may break during the manufacturing process of products such as displays. Therefore, the average thermal expansion coefficient at 50 to 350°C is 43×10 -7 / ℃ or less. The average thermal expansion coefficient between 50 and 350°C is 42×10 -7 / ℃ or less is preferable, and 41.5×10 -7 / ℃ or less is more preferable, and 41×10 -7 / ℃ or less is more preferable, and 40.5×10 -7 / ℃ or less is particularly preferable, and 40.3×10 -7 / °C or less is most preferable.

[0057] The specific elastic modulus of the glass of this embodiment (Young's modulus (GPa) / density (g / cm 3 ) is preferably 34 MN·m / kg or more. This reduces the self-weight deflection and makes it easier to handle when made into a large substrate. The specific elastic modulus is more preferably 34.5 MN·m / kg or more, even more preferably 34.8 MN·m / kg or more, particularly preferably 35 MN·m / kg or more, and most preferably 35.2 MN·m / kg or more.

[0058] The glass surface devitrification temperature (T c The glass surface devitrification viscosity (η c ) is 10 3.8 dPa·s or more is preferable. This provides excellent formability of the glass substrate. This also makes it possible to suppress the generation of crystals inside the glass during forming, which would otherwise cause a decrease in transmittance. This also makes it possible to reduce the burden on manufacturing equipment. For example, the life of float baths used to form glass substrates can be extended, improving productivity. Glass surface devitrification viscosity (η c ) is preferably 10 3.85 dPa·s or more, more preferably 10 3.9dPa·s or more, particularly preferably 10 4 dPa·s or more, most preferably 10 4.05 It is greater than or equal to dPa·s.

[0059] The viscosity of the glass of this embodiment is 10 2 The temperature T2 at which dPa·s is reached is preferably 1680°C or lower. This provides excellent glass melting properties. This also reduces the burden on manufacturing equipment. For example, the life of a furnace for melting glass can be extended, improving productivity. This also reduces furnace-derived defects (e.g., lumpy defects, Zr defects, etc.). T2 is more preferably 1670°C or lower, and even more preferably 1660°C or lower.

[0060] The glass transition point of the glass of this embodiment is preferably 730 to 790°C. When the glass transition point is 730°C or higher, the glass has excellent formability. For example, the thickness deviation and surface waviness can be reduced. In addition, when the glass transition point is 790°C or lower, the burden on the manufacturing equipment can be reduced. For example, the surface temperature of the roll used in forming the glass can be lowered, the life of the equipment can be extended, and the productivity can be improved. The glass transition point is more preferably 740°C or higher, even more preferably 745°C or higher, particularly preferably 750°C or higher, and most preferably 755°C or higher. On the other hand, the glass transition point is more preferably 785°C or lower, even more preferably 783°C or lower, particularly preferably 780°C or lower, and most preferably 775°C or lower.

[0061] The compaction of the glass of this embodiment is preferably 100 ppm or less, more preferably 90 ppm or less, even more preferably 80 ppm or less, even more preferably 75 ppm or less, particularly preferably 70 ppm or less, and most preferably 65 ppm or less. Compaction is the glass thermal shrinkage rate caused by relaxation of the glass structure during heat treatment. If the compaction is 100 ppm or less, it is possible to minimize the deformation of the glass and the dimensional change due to the stabilization of the glass structure when exposed to high temperatures in the thin film formation process carried out in the process of manufacturing various displays. In this embodiment, compaction refers to compaction measured in the following procedure. A glass plate sample (100 mm long x 10 mm wide x 1 mm thick sample mirror-polished with cerium oxide) obtained by processing the glass of this embodiment is held at a temperature of glass transition point + 120 ° C for 5 minutes, and then cooled to room temperature at 40 ° C per minute. When the glass plate sample is cooled to room temperature, the total length (lengthwise direction) L1 of the sample is measured. Then, the glass plate sample is heated to 600 ° C at 100 ° C per hour, held at 600 ° C for 80 minutes, and cooled to room temperature at 100 ° C per hour. When the glass plate sample is cooled to room temperature, the total length L2 of the sample is measured again. The ratio (L1-L2) / L1 of the difference in the total length before and after the heat treatment at 600 ° C to the total length L1 of the sample before the heat treatment at 600 ° C is taken as the value of compaction.

[0062] In the glass of the present embodiment, for example, the equivalent cooling rate is preferably 500° C. / min or less for the purpose of reducing compaction. The equivalent cooling rate is preferably 5° C. / min or more and 500° C. / min or less from the viewpoint of the balance between compaction and productivity. From the viewpoint of productivity, the equivalent cooling rate is more preferably 10° C. / min or more, even more preferably 15° C. / min or more, particularly preferably 20° C. / min or more, and most preferably 25° C. / min or more. From the viewpoint of compaction, the equivalent cooling rate is more preferably 300° C. / min or less, even more preferably 200° C. / min or less, particularly preferably 150° C. / min or less, and most preferably 100° C. / min or less. In this embodiment, the equivalent cooling rate means an equivalent cooling rate measured by the following procedure. A number of rectangular parallelepiped samples for creating a calibration curve, each measuring 10 mm x 10 mm x 1 mm, were prepared by processing the glass of this embodiment, and were held at the glass transition point +120°C for 5 minutes in an infrared heating electric furnace. After that, each sample was cooled to 25°C at different cooling rates ranging from 1°C / min to 1000°C / min. Next, the refractive index n of the d line (wavelength 587.6 nm) of each sample was measured using a precision refractometer KPR-2000 manufactured by Shimadzu Devices Corporation. d is measured by the V-block method.d By plotting against the logarithm of the cooling rate, the n d Obtain a calibration curve. Next, the glass of this embodiment is processed into a rectangular parallelepiped shape of 10 mm × 10 mm × 1 mm, and d is measured by the V-block method using a precision refractometer KPR-2000 manufactured by Shimadzu Devices. d The cooling rate corresponding to the above is determined from the calibration curve and is defined as the equivalent cooling rate.

[0063] The glass of this embodiment has a high Young's modulus of 88 GPa or more, and is suitable for use as a glass plate used as a large substrate because deformation of the substrate due to external stress is suppressed. A large substrate is, for example, a glass plate with at least one side of 1800 mm or more, and a specific example is a glass plate with a long side of 1800 mm or more and a short side of 1500 mm or more. The glass of the present embodiment is more preferably a glass plate having at least one side of 2400 mm or more, for example, a glass plate having a long side of 2400 mm or more and a short side of 2100 mm or more, more preferably a glass plate having at least one side of 3000 mm or more, for example, a glass plate having a long side of 3000 mm or more and a short side of 2800 mm or more, particularly preferably a glass plate having at least one side of 3200 mm or more, for example, a glass plate having a long side of 3200 mm or more and a short side of 2900 mm or more, and most preferably a glass plate having at least one side of 3300 mm or more, for example, a glass plate having a long side of 3300 mm or more and a short side of 2950 mm or more. The glass of this embodiment is preferably 0.7 mm or less in thickness because it is lightweight. The thickness of the glass of this embodiment is more preferably 0.65 mm or less, further preferably 0.55 mm or less, preferably 0.45 mm or less, and most preferably 0.4 mm or less. The thickness can be 0.1 mm or less, or 0.05 mm or less, but from the viewpoint of preventing deflection due to its own weight, the thickness is preferably 0.1 mm or more, and more preferably 0.2 mm or more.

[0064] The glass of the present embodiment can be produced, for example, by the following procedure. Glass raw materials are mixed to obtain a desired glass composition, charged into a melting furnace, and melted by heating to 1500 to 1800° C. The resulting molten glass is formed into a glass ribbon of a predetermined thickness in a forming device, and the glass ribbon is slowly cooled and then cut to obtain glass. In the production of the glass of this embodiment, in order to reduce compaction, it is preferable to cool the glass so that the equivalent cooling rate is 500° C. / min or less, for example.

[0065] In the production of the glass of this embodiment, it is preferable to form molten glass into a glass plate by a float method, a fusion method, etc. From the viewpoint of stably producing large plate glass (e.g., one side of 1800 mm or more) having a high Young's modulus, the float method is preferable.

[0066] Next, the display panel of this embodiment will be described. The display panel of the present embodiment has the above-mentioned glass of the present embodiment as a glass substrate. As long as it has the glass of the present embodiment, the display panel is not particularly limited, and may be various display panels such as a liquid crystal display panel or an organic EL display panel. Taking the case of a thin film transistor liquid crystal display (TFT-LCD) as an example, it has a display surface electrode substrate (array substrate) on whose surface a gate electrode line and a gate insulating oxide layer are formed, and further a pixel electrode is formed on the surface of the oxide layer, and a color filter substrate on whose surface a RGB color filter and a counter electrode are formed, and a cell is formed by sandwiching a liquid crystal material between the array substrate and the color filter substrate that form a pair. In addition to such a cell, a liquid crystal display panel includes other elements such as peripheral circuits. In the liquid crystal display panel of this embodiment, the glass of this embodiment is used for at least one of a pair of substrates that constitute the cell.

[0067] The glass of this embodiment can be used, for example, as a glass plate for supporting an electronic device. When the glass of this embodiment is used as a glass plate for supporting an electronic device, a device-forming substrate such as a glass substrate, a silicon substrate, or a resin substrate is supported on the glass of this embodiment (glass plate for supporting an electronic device) directly or by using an adhesive. Examples of the glass plate for supporting an electronic device include a supporting glass plate in a manufacturing process for a flexible display (e.g., an organic EL display) using a resin such as polyimide as a substrate, and a supporting glass plate for a resin-silicon chip composite wafer in a semiconductor package manufacturing process.

[0068] Next, the semiconductor device of this embodiment will be described. The semiconductor device of this embodiment has the above-mentioned glass of this embodiment as a glass substrate. Specifically, the semiconductor device of this embodiment has the glass of this embodiment as a glass substrate for image sensors such as MEMS, CMOS, CIS, etc. The semiconductor device of this embodiment also has the glass of this embodiment as a cover glass for a display device for projection use, for example, a cover glass for LCOS (Liquid Crystal on Silicon).

[0069] Next, the information recording medium of this embodiment will be described. The information recording medium of this embodiment has the above-mentioned glass of this embodiment as a glass substrate.Specific examples of the information recording medium include magnetic recording media and optical disks.Examples of the magnetic recording medium include energy-assisted magnetic recording media and perpendicular magnetic recording magnetic recording media.

[0070] Next, the planar antenna of this embodiment will be described. The planar antenna of this embodiment has the above-mentioned glass of this embodiment as a glass substrate. Specifically, the planar antenna of this embodiment is an antenna with good directivity and reception sensitivity, for example, a planar liquid crystal antenna having a planar shape such as a liquid crystal antenna or a microstrip antenna (patch antenna). The liquid crystal antenna is disclosed, for example, in International Publication No. 2018 / 016398. The patch antenna is disclosed, for example, in Japanese Patent Publication No. 2017-509266 and Japanese Patent Publication No. 2017-063255. EXAMPLES

[0071] Examples will be described below, but the present invention is not limited to these Examples In the following, Examples 1 to 22 and Examples 29 to 49 are Examples, and Examples 23 to 28 are Comparative Examples. The raw materials of each component were mixed so that the glass composition would be as shown in Tables 1 to 7 (unit: mol %), and melted in a platinum crucible at 1600°C for 1 hour. After melting, the molten liquid was poured onto a carbon plate and held at a temperature of glass transition point + 30°C for 60 minutes, and then cooled to room temperature (25°C) at 1°C per minute to obtain a plate-shaped glass. This was mirror-polished to obtain a glass plate, and various physical properties were measured. The results are shown in Tables 1 to 7. In Tables 1 to 7, the values ​​shown in parentheses are calculated values, and blanks indicate unmeasured values.

[0072] The methods for measuring each physical property are shown below. (β-OH value of glass) The glass sample was measured for absorbance at wavelengths of 2.75 to 2.95 μm, and the maximum value β max The β-OH value of the glass is calculated by dividing by the thickness (mm) of the sample.

[0073] (Average thermal expansion coefficient) Measurements were performed using a differential thermal expansion meter (TMA) according to the method specified in JIS R3102 (1995). The measurement temperature range was from room temperature to 400°C or higher, and the average thermal expansion coefficient from 50 to 350°C was calculated in units of 10. -7 Expressed as / °C. (density) According to the method specified in JIS Z 8807, the density of about 20 g of glass lump containing no bubbles was measured by the Archimedes method.

[0074] (distortion point) The strain point was measured by the fiber stretching method according to the method specified in JIS R3103-2 (2001). (glass transition temperature Tg) The glass transition point Tg was measured by the thermal expansion method using a differential thermal dilatometer (TMA) according to the method specified in JIS R3103-3 (2001). (Young's Modulus) According to the method specified in JIS Z 2280, the Young's modulus was measured by the ultrasonic pulse method for glass having a thickness of 0.5 to 10 mm.

[0075] (T2) The viscosity was measured using a rotational viscometer according to the method specified in ASTM C 965-96. 2 The temperature T2 (°C) at which the viscosity reached d·Pa·s was measured. (T4) The viscosity was measured using a rotational viscometer according to the method specified in ASTM C 965-96. 4 The temperature T4 (℃) at which the viscosity reached d·Pa·s was measured. (devitrification temperature) The glass was crushed and classified using a test sieve so that the particle size was in the range of 2 to 4 mm. The obtained glass cullet was ultrasonically cleaned in isopropyl alcohol for 5 minutes, washed with ion-exchanged water, dried, placed in a platinum dish, and heat-treated for 17 hours in an electric furnace controlled at a constant temperature. The heat treatment temperature was set at 10°C intervals. After heat treatment, the glass was removed from the platinum dish, and an optical microscope was used to measure the maximum temperature at which crystals precipitated on the surface and inside of the glass, and the minimum temperature at which no crystals precipitated. The maximum temperature at which crystals precipitated on the surface and inside of the glass, and the minimum temperature at which no crystals precipitated, were each measured once (two times were measured when it was difficult to determine whether crystals precipitated). The average value of the maximum temperature at which crystals precipitated on the glass surface and the minimum temperature at which no crystals precipitated was calculated to determine the glass surface devitrification temperature (T c Similarly, the average of the maximum temperature at which crystals precipitate inside the glass and the minimum temperature at which crystals do not precipitate was calculated to obtain the glass internal devitrification temperature (T d ) was decided.

[0076] (Specific elastic modulus) The specific elastic modulus was calculated by dividing the Young's modulus obtained by the above-mentioned procedure by the density. (devitrification viscosity) The glass surface devitrification temperature (T c ) and the glass surface devitrification temperature (T c The viscosity of the glass at the temperature was measured to obtain the glass surface devitrification viscosity (η c Similarly, the internal devitrification temperature (T d ) and the internal devitrification temperature (T d The viscosity of the glass at 100° C. was measured to obtain the internal devitrification viscosity (η d ) was decided.

[0077] [Table 1]

[0078] [Table 2]

[0079] [Table 3]

[0080] [Table 4]

[0081] [Table 5]

[0082] [Table 6]

[0083] [Table 7]

[0084] In Example 23, the Young's modulus was low, being less than 88 GPa. (T c ) was higher than T4+20℃. Examples 25, 27, and 28 had high strain points. Example 26, which had an RO of over 22, had a large average thermal expansion coefficient of 43×10 -7 / ℃.

[0085] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2018-46854) filed on March 14, 2018, and is incorporated by reference in its entirety. In addition, all references cited herein are incorporated in their entirety. [Industrial Applicability]

[0086] The glass of the present invention having the above-mentioned characteristics is suitable for applications such as display substrates, photomask substrates, electronic device support substrates, information recording medium substrates, and flat antenna substrates.

Claims

1. Density is 2.60 g / cm 3 The strain point is 650 to 710°C, the glass viscosity is 10 4 Temperature T at which viscosity becomes dPa·s 4 is 1320°C or less, glass surface devitrification temperature (T c ) is T 4 Average thermal expansion coefficient below +20℃ and between 50 and 350℃ is 30×10 -7 ~43×10 -7 / °C, The specific elastic modulus is 34 MN·m / kg or more, In mole percent based on oxide SiO 2 64 to 70% Al 2 O 3 を10~14%、 MgO: 8.5 to 13% CaO 6 to 10%, Li 2 O, Na 2 O and K 2 O, P 2 O 5 0 to 1%, Including glass.

2. Glass surface devitrification viscosity (η c ) is 10 3.8 2. The glass of claim 1, wherein the viscosity is ≥ 100 dPa·s.

3. Viscosity is 10 2 Temperature T at which viscosity becomes dPa·s 2 3. The glass according to claim 1, wherein the melting point of the glass is 1680° C. or less.

4. The glass according to any one of claims 1 to 3, having a glass transition point of 730 to 790°C.

5. In mole percent based on oxide B 2 O 3 0 to 5%, SrO 0 to 10%, BaO 0 to 10%, Na 2 Oを0.005~0.2%、 F: 0.001 to 0.5%; Li 2 O, Na 2 O and K 2 O. The glass according to any one of claims 1 to 4, wherein MgO + CaO + SrO + BaO is 22% or less.

6. 6. The glass according to claim 5, wherein MgO / CaO is 0.85 to 1.

33.

7. β-OH value is 0.1 to 0.6 mm -1 The glass according to any one of claims 1 to 6,

8. The glass according to any one of claims 1 to 7, wherein the value represented by the following formula (I) is 4.10 or more: (7.87) [Al 2 Oh 3 ]-8.5[B 2 Oh 3 ]+11.35[MO]+7.09[1O]+5.52[SrO]-1.45[BaO]) / [SiO 2 ]・・・form (I)

9. The glass according to any one of claims 1 to 8, wherein the value represented by the following formula (II) is 0.95 or more: {-1.02[Al 2 O 3 +10.79[B 2 O 3 +2.84[MgO]+4.12[CaO]+5.19[SrO]+3.16[BaO]+11.07×([Li 2 O]+[Na 2 O]+[K 2 O])+3.954[F]+5.677[β-OH]} / [SiO 2 ... Formula (II)

10. The glass according to any one of claims 1 to 9, wherein the value represented by the following formula (III) is 5.5 or less. (8.9[Al 2 O 3 + 4.26[B 2 O 3 + 11.3[MgO] + 4.54[CaO] + 0.1[SrO] - 9.98[BaO]) × {1 + ([MgO] / [CaO] - 1) 2} / [SiO 2 ... Formula (III)

11. In terms of oxide mol%, SnO 2 The glass according to any one of claims 1 to 10, containing 0.5% or less of

12. 12. The glass according to claim 1, having a compaction of 100 ppm or less.

13. The glass according to any one of claims 1 to 12, having an equivalent cooling rate of 5 to 500°C / min.

14. The glass according to any one of claims 1 to 13, which is a glass plate having at least one side of 1800 mm or more and a thickness of 0.7 mm or less.

15. 15. The glass of claim 14 produced by a float process or a fusion process.

16. A display panel comprising the glass according to any one of claims 1 to 15.

17. A semiconductor device comprising the glass according to any one of claims 1 to 15.

18. An information recording medium comprising the glass according to any one of claims 1 to 15.

19. A planar antenna comprising the glass according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Heat insulating device for electrolytic cell

    JP1982002888A

  • Movable nursery plant placing-on frame of riding type rice transplanter

    JP1982012922A

  • Copying apparatus

    JP1983049965A

  • Portable information device

    JP2007228446A

  • Portable communication terminal

    JP2012090206A